KPJ Tawakkal KL Specialist Hospital / Zulaiqa Mohd Jamal Abdul Nasir - Mohd Jamal Abdul Nasir, Zulaiqa (Universiti Teknologi MARA, Perlis, 2023)
This report was made for the things I have done during my internship, starting from 1 March 2023 until 15 August 2023. As a degree student of Bachelor of Business Administration (Hons) Human Resources Management, we were required to through a six-month practical training to prepared ourselves for future working environment. KPJ Tawakkal KL Specialist Hospital was one of the plenty companies I applied to for internship placement and being one of the two that accepted my application. In this report I will includes my resumes, the KPJ Tawakkal Specialist Hospital background, vision and mission, their organisation structure, my internship journey and also the SWOT analysis regarding the company. In the discussion part, I have discussed the SWOT Matrix based on the SWOT analysis and the recommendation that possibly be done to improve the weakness and overcome the threat exist inside the company.